Effects of various heat treatment cycles on mechanical properties and wear resistance of 65Mn carbon steel - MOJAHEDI, Amir Abbas; SAJJADI, Seyed Abdolkarim; SAYYEDAN, Fatemehsadat (Journal of Metals, Materials and Minerals, 2026)
The aim of the present study is to investigate the effect of various heat treatment cycles on mechanical properties and wear resistance of 65Mn carbon steel. For this purpose, five different heat treatment cycles including normalizing, austenitizing, quenching, and tempering were performed at different austenitization temperatures and tempering times. Subsequently, effects of the parameters on tensile strength, toughness, hardness, and wear resistance of the heat-treated samples were investigated. X-ray diffraction (XRD) and scanning electron microscopy (SEM) equipped with energy dispersive X-ray spectroscopy (EDS) were employed to analyze microstructure of heat-treated samples. To study the wear resistance of the samples after heat treatment, pin-on-disk wear test was conducted. The results revealed that the optimal mechanical and wear properties, including a hardness of 723 HV, a tensile strength of 1062 MPa, a fracture toughness of 14.7 J∙cm‒2, and a weight loss of 0.001 g, were achieved after the heat treatment cycle of normalizing at 850℃ for 30 min, austenitizing at 780℃ for 30 min, oil quenching, and then tempering at 200℃ for 60 min. These results were obtained due to the achievement of a two-phase martensite-ferrite microstructure with the minimum initial austenite grain size among different austenitization temperatures.